Novel angiotensin I-converting enzyme inhibitory peptides from soybean protein isolates fermented by Pediococcus pentosaceus SDL1409. (July 2018) - Daliri, Eric Banan-Mwine; Lee, Byong H.; Park, Mi Houn; Kim, Jong-Hak; Oh, Deog-Hwan
Abstract: In this study, Pediococcus pentosaceus SDL1409 was used to ferment soybean protein isolates for 48 h at 37 °C. Low molecular weight peptides (≤7 KDa) from the fermented sample showed strong angiotensin I-converting enzyme inhibitory ability of 65.1 ± 0.78% (IC50  = 0.123 ± 0.02 mg protein/ml). The low molecular weight peptides were identified using liquid chromatography-electrospray ionization quantitative time-of-flight mass spectrometry analysis. On the basis of peptide abundance and common structural features, four peptides were selected and chemically synthesized. The peptides namely EDEVSFSP, SRPFNL, RSPFNL and ENPFNL showed strong IC50 values of 0.571 ± 0.12, 0.131 ± 0.02, 0.811 ± 0.05 and 0.287 ± 0.07 mg/mL respectively. EDEVSFSP was fairly resistant to gastrointestinal enzyme digestion. The presence of P/FNL, the N-terminal sequence as well as the position of amino acids in the peptides were essential for ACE inhibition. Our data demonstrate that Pediococcus pentosaceus SDL1409 could be useful for developing antihypertensive functional foods from soybean proteins. Graphical abstract: Highlights: Food proteins encrypt bioactive peptides which can be release by fermentation. P. pentosaceus SDL1409 released EDEVSFSP, SRPFNL, RSPFNL and ENPFNL from soy proteins. The peptides showed strong angiotensin I-converting enzyme activity. The LAB could be useful for developing antihypertensive functional foods.